A Hydrophilic Channel Is Involved in Oxidative Inactivation of a [NiFeSe] Hydrogenase - Zacarias, Sónia (2019)
Hydrogenases are metalloenzymes that catalyze the redox conversion between H2 and protons. The so-called [NiFeSe] hydrogenases are highly active for both H2 production and oxidation, but like all hydrogenases, they are inhibited by O2. In the [NiFeSe] enzyme from Desulfovibrio vulgaris Hildenborough this inhibition results from the oxidation of an active site cysteine ligand. We designed mutations that constrict a hydrophilic channel which connects the protein surface to this active site cysteine. Two of the variants show markedly increased tolerance to O2 inactivation, while they retain high catalytic activities in both directions of the reaction, and structural studies confirm that these mutations prevent the oxidation of the cysteine. Our results indicate that the diffusion of O2 or ROS to the active site can occur through a hydrophilic water channel, in contrast to the widely held assumption that only hydrophobic channels are involved in active site inactivation. This provides an original strategy for optimizing the enzyme by protein engineering.